Identifying potential nutrient acquisition mechanisms for long-term survival: adaptive evolution of Halomonas isolated from subseafloor crustal fluids - Sebastian, Hans; Robador, Alberto; Ray, Dawson; Angermeyer, Angus; D’Hondt, Steven; Huber, Julie A.; Finkel, Steven E. (Frontiers in Microbiology, 2025)
In nature, microbes must often survive for long periods of time under conditions of nutrient and carbon limitation while also facing extremes in temperature, pressure, and competition with other microbes. One low-carbon, cold, and high pressure environment is the subseafloor crustal aquifer, where fluids circulate through old ocean crust. While microbial communities are known to be present in these fluids and contribute to biogeochemical cycling, the survival strategies of microbes in these communities is poorly constrained. In this study, multiple Halomonas strains were isolated from subseafloor crustal fluids of North Pond, a site located on the western flank of the Mid-Atlantic Ridge. These organisms are able to grow under laboratory conditions in minimal medium without the addition of carbon sources, as well as in rich nutrient conditions. We found that these Halomonas strains are highly related to each other in genomic content, but each strain has acquired unique mutations and/or undergone genomic rearrangements, suggesting that the strains were all derived from a single ancestral Halomonas progenitor. After serial passage of isolates from this Halomonas population under rich nutrient conditions in the laboratory, we identified mutants that can no longer scavenge scarce nutrients in minimal medium with no added carbon. Genomic analysis identified several genes that appear to be essential for survival under extremely low-nutrient condition, including several hypothetical proteins predicted to function as lipases, peptidases, or nutrient transporters. One of these genes was mutated in six out of the eight lineages studied, indicating that this hypothetical lipase protein is selected against during growth in rich medium, but may be required for growth under low-nutrient conditions. The application of an adaptive evolution platform selecting for survival and growth under one environmental condition that simultaneously selects against survival in different environments may prove to be a very useful tool for identifying genes and metabolic pathways in a wide variety of complex environments.